Plug in 10 for x in h(x) then simplify
h(10)=2(10)-8
h(10)=20-8
h(10)=12
h(10) is 12 so put 12 in for g(x)
g(h(10))=12-4
g(h(10))=8
Here’s everything together
g(h(10))=(2(10)-8)-4
=(20-8)-4
=(12)-4
=8
This is what I’ve always done. I can’t really tell what your answers are so sorry if this isn’t right at all.
BEHJEJEBEHRUUE what is this eheujrf
Simply the answer is 12 and 8.
Mark brainliest please
Hope this helps you
Answer:
...Sorry but I dont get the problem can you please clarify the problem..
Step-by-step explanation:
Answer:
I am 99.99% sure it is the first one